Dosage Effects of an 810 nm Diode Laser on the Proliferation and Growth Factor Expression of Human Gingival Fibroblasts: Dose Effects of an 810 nm Diode on Gingival Fibroblasts - Karoussis, Ioannis K.; Kyriakidou, Kyriaki; Psarros, Costas; Afouxenides, Panayotis; Vrotsos, Ioannis A. (Journal of Lasers in Medical Sciences, 2021)
Introduction: A substantial amount of evidence supports the positive effect of photobiomodulation on the proliferation and differentiation of various cell types. Several laser wavelengths have been used for wound healing improvement, and their actual outcome depends on the settings utilized during irradiation. However, the heterogeneous wavelengths and laser settings applied in the existing literature make it difficult to draw solid conclusions and comparison of different studies. The aim of the present study is to evaluate and compare the effects of various doses of laser energy, provided by an 810 nm diode, on human gingival fibroblasts in terms of proliferation and expression of growth factors with a pivotal role in wound healing. Methods: Human gingival fibroblasts were cultured on plastic tissue culture and irradiated with 2, 4, 6 or 12 J/cm2. The effects of the low-level laser therapy (LLLT) using an 810 nm diode laser on growth factor expression (EGF, TGF and VEGF) were evaluated by qPCR at 72 hours and 7 days after irradiation. Cell proliferation was evaluated at 24, 48 and 72 hours after LLLT using MTT assay. Results: Energy density of 12 J/cm2 provoked irradiated gingival fibroblasts to demonstrate significantly higher proliferation as well as higher gene expression of Col1, VEGF and EGF. LLLT positive effects were obvious up to 7 days post-irradiation. Conclusion: LLLT with 810 nm presents beneficial effects on proliferation, collagen production and growth factor expression in human gingival fibroblast cells. The application of 12 J/cm2 can be suggested as the optimal energy density for the enhancement of the wound healing process. DOI: 10.34172/jlms.2021.25